(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
of teachers in implementing learning, in accordance with the field of study that is their responsibility. Teacher readiness is shown pedagogically, namely in choosing and determining the right learning model, in accordance with the subject matter and characteristics of students. Initial data on science learning in class V MIN 26 Aceh Besar, showed that most of the students’ learning outcomes had not been able to achieve the KKM (Minimum Completion Criteria), which was 70. The purpose of this study is to analyze teacher and student activities, as well as student learning outcomes using the Arends time token learning model in IPAS learning in elementary schools. The research method used was classroom action research. Data collection was carried out in accordance with the stages of classroom action research, namely planning, implementation, observation, and reflection of learning, as well as assessment of student learning outcomes. The results of the study found that teacher activity in cycle I was categorized as good (79.00%), while in cycle II teacher activity increased very well (91.40%). Student activity in cycle I was categorized as good (78.10%), while in cycle II student activity experienced a very good increase (92.40%). Student learning outcomes in cycle I were completed (53.33%). In cycle II student learning outcomes increased by achieving a complete score (86.70%). The results of the cycle I and cycle II tests showed that the application of the Time Token Arends learning model could improve student learning outcomes at MIN 26 Aceh Besar. Analysis of the results of this study showed that active participation in student learning through the application of the time token Arends learning model correlated with the improvement and strengthening of student understanding of the material taught by the teacher, which was indicated by an increase in student learning outcomes. Keywords: Time token arends, learning outcomes